Capacity Building Remaja Masjid di Wilayah Kelurahan Sawojajar Kecamatan Kedungkandang Kota Malang - Yuniar, Rendhi Fatrisna; rosi, rois imron; Setyaningrum, Ikha Sulis (JRCE (Journal of Research on Community Engagement), 2025)
The Capacity Building program for Youth Mosques held on September 22, 2024, at Masjid Miftahul Jannah, Sawojajar, represented an initiative by UIN Maulana Malik Ibrahim Malang to prepare youth as competent mosque leaders. This program was motivated by concerns from mosque administrators regarding the lack of youth ready to lead congregational prayers and master the procedures for becoming an imam, particularly in the Sawojajar area. The event focusing on enhancing Quranic reading skills and understanding the principles of Imamah (the role of an imam). Ustadz Choirul Amin, a student of Pesantren Ilmu Al-Quran, provided intensive training in Quranic recitation, while Ustadz Muallif, M.Ag., taught Fiqh Imamah as a lecturer at Ma'had Aly UIN Malang. This initiative engaged youth from various mosques and prayer rooms in Sawojajar, collaborating with local youth organizations such as Karang Taruna. The primary goal was to prepare youth to become imams who are proficient in Quranic reading and capable of leading prayers according to Islamic teachings. The program received positive feedback from Ir. Sunaryo, the head of the mosque's management, who noted its role in addressing the need for generational renewal among mosque administrators, historically dominated by older generations.